Design optimization of structures under fatigue loading - Ertaş, Ahmet Hanifi. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Many of the engineering failures are caused by fatigue. Fatigue failure can be defined as the tendency of a material to fracture by means of progressive brittle cracking under cyclic stresses. Because mechanical components usually experience cyclic loading during their operation, fatigue failure prevention is the foremost design requirement. Fatigue strength, thus structural performance, can greatly be increased through design optimization. Hence in this study, the general objective is to maximize the fatigue life of structures. Firstly, high cycle fatigue assessment models for homogeneous materials were investigated. Then, they were applied to predict fatigue lives of spot welded specimens. Reliability of these models depends on accurate calculation of the cyclic stress and strain states within the structure. For this purpose, a nonlinear finite element analysis was carried out taking into account plastic deformations, residual stresses developed after unloading, and contacting surfaces. Among the general purpose fatigue models, Coffin - Manson and Morrow’s mean stress models were found to correlate best with the experimental data. After that, a parametric study on fatigue strength of spot weld joints was conducted. The design variables considered in this study that were known to affect the strength of spot weld joints were sheet thickness, spot weld nugget diameter, number of spot welds, and the joint type as exemplified in tensile shear (TS), modified tensile shear (MTS), coach peel (CP), and modified coach peel (MCP) specimens. The results provide designers with some guidelines to foresee the impact of design changes on fatigue strength of spot weld joints. Secondly, a methodology was proposed to find the optimum locations of spot welds and the optimum overlapping length of the joined plates for maximum fatigue life. Minimum weld-to-weld and weld-to-edge distances recommended by the industry were considered as side constraints. The total strain life equation was used to predict the fatigue life. In order to use this model, the strain state in the structure developed under cyclic loading was calculated. Nelder-Mead (Sequential Simplex) was employed as the search algorithm in the optimization procedure. A number of problems were solved to demonstrate the effectiveness of the proposed method. Finally, a methodology was developed to optimize composite laminates subject to inplane loads for maximum fatigue life. For this purpose, a parametric fatigue life prediction model, proposed by Fawaz and Ellyin, was coupled with a global optimization technique called Direct Simulated Annealing (DSA). Fiber orientation angles were chosen as design variables. A computer code was developed in ANSYS parametric language and results were obtained for different configurations and loading conditions.
Keywords: System failures (Engineering).; Materials -- Fatigue.